Multi-color super-resolution imaging to study human coronavirus RNA during cellular infection - Wang, Jiarui; Han, Mengting; Roy, Anish R.; Wang, Haifeng; Möckl, Leonhard; Zeng, Leiping; Moerner, W. E.; Qi, Lei S. (Cell Reports: Methods, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the third human coronavirus within 20 years that gave rise to a life-threatening disease and the first to reach pandemic spread. To make therapeutic headway against current and future coronaviruses, the biology of coronavirus RNA during infection must be precisely understood. Here, we present a robust and generalizable framework combining high-throughput confocal and super-resolution microscopy imaging to study coronavirus infection at the nanoscale. Using the model human coronavirus HCoV-229E, we specifically labeled coronavirus genomic RNA (gRNA) and double-stranded RNA (dsRNA) via multi-color RNA immunoFISH and visualized their localization patterns within the cell. The 10-nm resolution achieved by our approach uncovers a striking spatial organization of gRNA and dsRNA into three distinct structures and enables quantitative characterization of the status of the infection after antiviral drug treatment. Our approach provides a comprehensive imaging framework that will enable future investigations of coronavirus fundamental biology and therapeutic effects.
CRIS-Team Scopus Importer:2024-09-09
Keywords: coronavirus infection model; ER remodeling; FISH; fluorescence imaging; human coronavirus 229E; Remdesivir; RNA localization; spike protein; super-resolution microscopy; viral replication and infection